A SURVEY OF LITERATURE: MONETARY POLICY TRANSMISSION MECHANISM IN INDIA - Kumar, Praveen; Ranawat, Mahendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The literature review is significant in understanding the past evolution and the current state of knowledge regarding the given discipline or subject. However, every research article published by anyone contains certain part of literature review concerned with their respective area of study. The main aim the study is to provide the comprehensive review of literature regarding monetary policy transmission mechanism in India. For this purpose, the paper will be reviewed on the basis of four parameters i.e., variables used, theoretical models used for estimation, methodology and tools used and findings of the study.